1971
DOI: 10.1007/bf01254169
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunoelectrophoretic identification of poliovirus inhibitors and their characteristic mode of action

Abstract: SummaryPoliovirus inhibitors present in normal equine and bovine sera were studied by means of radioimmunoeleetrophoresis and column chromatography. The inhibitors in individual equine sera were identified as either one of the three immunoglobulins, yM, yA(T) and yG, or mixtures of them, while those in bovine sera were found to be either one of yM and yG globulins, or the mixture of the two.The inhibitors belonging to different classes of immnnoglobulin differed in their mode of action against the virus, yM in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…prep~ring t~e .abovementioned neutralizing antibodies and of the differences m their specificity are described in the previous paper (15). Neutralizing antibody titers were determined by plaque reduction assay as described previously (14).…”
mentioning
confidence: 99%
“…prep~ring t~e .abovementioned neutralizing antibodies and of the differences m their specificity are described in the previous paper (15). Neutralizing antibody titers were determined by plaque reduction assay as described previously (14).…”
mentioning
confidence: 99%
“…A similar sero-epidemiologic observations have been made by various investigators on the NT activity in various animal sera against polio viruses and other enteroviruses (Takemori et al, 1958;Ackerman and Dinka, 1965;Pagano, Gilden and Sedwick, 1965;Urasawa and Kanamitsu, 1971;Takemoto and Habal, 1959;Thomssen, Gerrit and Andreas, 1966;Bartell and Klein, 1955;Svehag, 1964) and recently against insect picornaviruses which have similar characteristics with animal enteroviruses (Longworth et al, 1973;Scotti and Longworth, 1980). One of the common features of these NT substances was that they were found to belong to IgM except in one study in which NT activity against poliovirus was found both in IgG and IgM fractions of horse and bovine sera (Urasawa et al, 1971).…”
Section: Discussionmentioning
confidence: 56%
“…One of the common features of these NT substances was that they were found to belong to IgM except in one study in which NT activity against poliovirus was found both in IgG and IgM fractions of horse and bovine sera (Urasawa et al, 1971). Most of the investigators have considered these NT substances likely to be antibody.…”
Section: Discussionmentioning
confidence: 99%
“…The mixture was then processed for electron microscopy as described previously (Taniguchi et al, 1981). Neutralizing antibody titres were determined by 50~o plaque reduction assay as previously described (Urasawa et al, 1971).…”
Section: Discussionmentioning
confidence: 99%